A case for institutional demand as effective social protection: Supporting smallholders through procurement and food assistance programmes - Ryan Nehring; Ana Carla Miranda; Andrew Howe (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
This paper focuses on the rationale for state-based market interventions to support smallholder production along with some case studies that follow the evolution and impact of what we call 'institutional demand' policies. Institutional demand is an intervention that aims to improve regional markets by establishing coordinated purchases for regional distribution, primarily through local and regional food procurement (LRP). We also address the question of smallholder farmers' dependency on state-based market interventions, and review existing evidence of how institutional purchase programmes have supported income generation and increased agricultural production. The paper outlines the two direct forms of social protection offered through institutional demand: reliable income generation for targeted smallholders and expanded food availability for vulnerable populations. Our hope is that this paper will outline areas for future research to analyse the impact of institutional demand policies.
Keywords: 330; case; institutional; demand; effective; social protection; supporting; smallholders; procurement; food assistance; programmes